SECI Model in Technical Education and Entrepreneurship: A Systematic Review of Knowledge Creation Enablers - Bonita Destiana; Mochamad Bruri Triyono (LP. Ma'arif Janggan Magetan, 2026)
This paper is a systematic literature review of the SECI model in technical education, entrepreneurship and organizational settings. Although the SECI model has been widely applied to explain knowledge creation, prior studies have predominantly emphasized its structural, procedural, and technological extensions, while giving less attention to the relational and motivational factors that shape knowledge-sharing processes. Using PRISMA guidelines, Scopus-indexed empirical studies published between 2016 and 2025 were systematically identified, screened, and selected based on their explicit application of SECI and their relevance to innovation, learning or performance outcomes. A total of 21 studies were synthesized into four themes: (1) the role of SECI in competency development in technical education, (2) the application of SECI in entrepreneurial and product innovation contexts, (3) relational, psychological, and cultural enablers of knowledge creation, and (4) the adaptation and evolution of the SECI model. The findings indicate that SECI supports competency development, innovation processes, and organizational performance. Furthermore, its effectiveness is strongly influenced by relational and motivational factors such as trust, intrinsic motivation, and interpersonal interaction. This review offers an integrative conceptual understanding of SECI that foregrounds relational and motivational factors as foundational conditions for effective knowledge creation in technical education and entrepreneurial ecosystems.